Analysis of Rahn Law an Islamic Economic Perspective - Deni Yuliono; Hadi Sunaryo; Pardiman Pardiman (Jurnal Ilmiah Ekonomi Islam, 2023)
The development of the Islamic financial system gave rise to Islamic financial institutions, one of whose products is pawnshops. Pawnshops in sharia are known as Rahn which means pawn. Rahn or Pawn is a binding agreement between the creditor and the debtor in a loan and loan transaction by placing collateral on the debt. The purpose of this article is for the Analysis of the Implementation of rahn Law (pawn) in an islamic economic perspective. The method used using a skinative model with an Islamic economic approach and the analysis used is descriptive analysis. The study results show that rahn is allowed in Islamic teachings, its development has also become increasingly prevalent. Rahn is used as an economic support for people in need. The rahn law has also been allowed by islamic clerics and fatwas. However, its activities must be by the conditions, harmony and applicable policies.